Distribution of Methane Plumes on Cascadia Margin and Implications for the Landward Limit of Methane Hydrate Stability - Merle, Susan G.; Embley, Robert W.; Johnson, H. Paul; Lau, T.-K.; Phrampus, Benjamin J.; Raineault, Nicole A.; Gee, Lindsay J. (Frontiers in Earth Science, 2021)
Nearly 3500 methane bubble streams, clustered into more than 1300 methane emission sites, have been identified along the US Cascadia margin (USCM), derived both from archived published data and 2011, 2016-2018 dedicated multibeam surveys using co-registered seafloor and water column data. In this study, new multibeam sonar surveys systematically mapped nearly 40% of the US Cascadia margin, extending from the Strait of Juan de Fuca in the north to the Mendocino fracture zone in the south, and bounded East-West by the coast and the base of the accretionary prism. The frequency-depth histogram of the bubble emission sites has a dominant peak at the 500 m isobar, which extends laterally along much of the Cascadia margin off Oregon and Washington. Comparisons with published seismic data on the distribution of bottom simulating reflectors (BSR), ¬¬¬-which is the acoustic impedance boundary between methane hydrate (solid phase) and free gas phase below, correlates the BSR’s upward termination of the FEMHS zone and the newly-identified bubble emission sites off Oregon and Washington. The Cascadia margin off northern California, where the BSR ends seaward of the FEMHS, has fewer sites centered on the 500 m isobaths, although data are more limited there. We propose that the peak in bubble emission sites observed near the 500 m isobath results from migration of free gas from beneath the solid phase of the BSR upslope to the FEMHS termination zone, and suggest that this boundary will be useful to monitor for a change in methane release rate potentially related to a warming ocean.